PSYCHOLOGICAL DESCRIPTION (STRESS) OF NURSES IN CARING FOR COVID-19 PATIENTS - erna marni; rani lisa indra (LPPM Universitas Abdurrab, 2021)
The nursing profession is a health profession that has an important influence on health services, during the Covid-19 pandemic, nurses are the most vulnerable profession, both the risk of infection from the patient being treated and the recession of psychological disorders such as stress, considering that nurses are facing patients 24 hours will have the greatest impact both physically and psychologically. This study aims to see the psychological picture (stress) of nurses caring for Covid-19 patients. The research method used is a type of quantitative research with analytic descriptions, with a survey method. The population of this study was all nurses who served in the Covid-19 room in Riau province with a total sample of 50 nurses. The sampling technique used a survey method, using a questionnaire via Google Form. The results obtained were normal 43 respondents (86%), light stress 5 respondents (10%), and moderate stress 2 respondents (4%). From these results, it is known that 14% of respondents experienced mild and moderate stress. It is hoped that the hospital can pay attention to the psychological condition of nurses by facilitating/giving nurses time for relaxation or making refreshing programs to reduce the risk of stress on nurses.